Passenger Terminal Safety: Simulation Modelling as Decision Support Tool. (2016) - (Jackiva), Irina Yatskiv; Savrasovs, Mihails; Gromule, Vaira; Zemljanikins, Valerijs
Abstract: The paper demonstrates the possibility of using simulation modelling for improving the processes of managing the development of the terminal at a strategic level, taking into account, first of all, security and safety aspects of quality of services. The described in the paper developed simulation model based on the AnyLogic software could be treated as decision support tool for management of the passenger terminal. The background of the problem is related with the started reconstruction process of the terminal with no ability to close it for reconstruction period. The decision to temporary close different parts of the platforms and make step-by-step reconstruction was done by management. But this decision causes a number of question regarding safety aspects of the passengers. The developed simulation model is directed on estimation of the passengers' density in terminal. The higher density directly influences the safety issues. The primary task of the developed decision support tool is to support management of the terminal with quantitative values of passenger density for different scenarios of reconstruction.